Multilayer polyethylene film

By using high content recovery of polyethylene and multimodal ethylene terpolymers in multilayer polyethylene films, combined with coextrusion process, the problem of insufficient performance of recycled plastic films in packaging applications is solved, and high mechanical performance and low The film sealed at the starting temperature promotes the effective use of recycled plastics.

CN119173390AActive Publication Date: 2024-12-20BOREALIS AG
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380039656.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-17
Filing Date
2023-05-16
Publication Date
2024-12-20
Estimated Expiration
2043-05-16

AI Technical Summary

Technical Problem

Existing recycled plastic films show limited impact strength and mechanical properties in packaging applications, and are difficult to meet customers' requirements for toughness, tensile strength and aesthetic performance. At the same time, the performance of recycled plastics is poor when mixed with native plastics is difficult to achieve high efficiency. Recycling.

Method used

Using a multi-layer polyethylene film structure, the core layer consists of high content recovery polyethylene, multimodal ethylene terpolymer and polyethylene, and different units in the polymer chain are identified and quantified by quantitative 13C{1H}NMR measurement, and optimized Polymer component ratios to improve mechanical and optical properties and form films by coextrusion processes.

Benefits of technology

A multi-layer polyethylene film with improved mechanical properties and low sealing starting temperature is realized, allowing large quantities of recycled polyethylene to be used without reducing performance, meeting the needs of packaging applications, and improving the recycling rate of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127688380000171
    Figure BDA0005127688380000171
  • Figure BDA0005127688380000211
    Figure BDA0005127688380000211
  • Figure BDA0005127688380000221
    Figure BDA0005127688380000221
Patent Text Reader

Abstract

The present invention relates to a multilayer polyethylene film comprising a skin layer, a sealing layer and a core layer located between the skin layer and the sealing layer wherein the core layer comprises a core layer composition comprising: recycled polyethylene having an MFR2 as determined according to ISO 1133 of from 0.1 to 2.0 g / 10 min and a density as determined according to ISO 1183 of from 910 to 930 kg / m3, a multimodal ethylene terpolymer having a density as determined according to ISO 1133 of from 0.1 to 2.0 g / 10 min and a density as determined according to ISO 1183 of from 910 to 930 kg / m3, a polyethylene having an MFR2, determined according to ISO 1133, of from 0.5 to 2.0 g / 10 min and a density, determined according to ISO 1183, of from 910 to 930 kg / m3, and a polyethylene having an MFR5, determined according to ISO 1133, of from 0.1 to 2.5 g / 10 min and a density, determined according to ISO 1183, of from 925 to 950 kg / m3. The invention also relates to a method for producing said multilayer polyethylene film, to the use of said core layer composition as a core layer in a multilayer polyethylene film for improving haze and SIT of a multilayer polyethylene film, and to articles comprising such a multilayer polyethylene film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multilayer polyethylene film, comprising a surface layer, a sealing layer and a core layer located between the surface layer and the sealing layer. The present invention also relates to a method for producing a multilayer polyethylene film, a core layer composition and use of the core layer composition as a core layer in a multilayer polyethylene film, and an article comprising the core layer composition or the multilayer polyethylene film. Background Art

[0002] Polyethylene-based materials are a particular problem, as these are widely used in packaging. Considering the huge amount of waste collected compared to the amount recycled into the stream, there is still a lot of potential for the smart reuse of plastic waste streams and for the mechanical recycling of plastic waste.

[0003] It is therefore important to develop a circular economy that gives plastic waste a second life, i.e. recycling, which not only avoids leaving plastic waste in the environment but also restores its value.

[0004] In addition, the European Commission confirmed in 2017 that it would focus on the production and use of plastics. The EU's goals are: 1) by 2025, at least 55% of all plastic packaging in the EU should be recycled; 2) by 2030, all plastic packaging on the EU market should be reusable or easily recyclable. This has prompted brand owners and plastic processors to seek solutions using recycled materials or a mix of virgin / recycled materials.

[0005] Therefore, polymers obtained from waste materials are increasingly important in the manufacture of new products, i.e. waste plastics, such as post-consumer recycled material (PCR), can be converted into a resource for new plastic products. Thus, environmental and economic aspects can be combined when recycling and reusing waste plastic materials.

[0006] However, the quality of recycled plastics is usually inferior to that of virgin plastics due to degradation, contamination and mixing of different plastics. However, for packaging applications, a balanced behavior of film impact strength (e.g. dart impact strength) and mechanical properties (e.g. toughness, tensile strength) as well as good aesthetic properties (e.g. haze and clarity) is ideal. In addition, sealing properties are also an important requirement in packaging applications.

[0007] In addition, compositions containing recycled polyolefin materials generally have much worse properties than virgin materials unless the amount of recycled polyolefin added to the final composition is extremely low. For example, such materials generally have limited impact strength and poor mechanical properties, so they cannot meet customer requirements.

[0008] Mixing recycled plastic with virgin plastic is a common practice to improve the quality of recycled plastic. Summary of the invention

[0009] It is therefore an object of the present invention to provide a multilayer polyethylene film which is partly made of recycled polyethylene, in particular to provide a multilayer polyethylene film comprising a core layer which is partly made of recycled polyethylene.

[0010] Another object of the present invention is to provide a multilayer polyethylene film having good mechanical properties, in particular toughness, while having improved optical properties, such as haze.

[0011] Another object of the present invention is to provide a multilayer polyethylene film having good sealing properties, ie having a low seal initiation temperature (SIT).

[0012] Finally, it is an object of the present invention to provide a core layer composition for a multilayer film which allows the use of recycled polyethylene, in particular the use of recycled polyethylene in large amounts in the core layer composition.

[0013] Therefore, the present invention provides a multilayer polyethylene film, which comprises a surface layer, a sealing layer and a core layer located between the surface layer and the sealing layer, preferably composed of a surface layer, a sealing layer and a core layer located between the surface layer and the sealing layer,

[0014] The core layer comprises a core layer composition or consists of a core layer composition, wherein the core layer composition comprises the following components, preferably consists of the following components:

[0015] a) Recycled polyethylene having an MFR2 of 0.1 to 2.0 g / 10 min, measured according to ISO 1133, and a density of 910 to 930 kg / m 3 ,

[0016] b) a multimodal ethylene terpolymer having an MFR2 of from 0.5 to 2.0 g / 10 min, measured according to ISO 1133, and a density of from 910 to 930 kg / m 3 , MWD determined by GPC (gel permeation chromatography) is 2.0 to 7.5,

[0017] c) Polyethylene having an MFR5 of 0.1 to 2.5 g / 10 min, measured according to ISO 1133; a density of 925 to 950 kg / m 3 ; MWD determined by GPC (gel permeation chromatography) is 8.0 to 35.0.

[0018] The present invention is based on the discovery that multilayer polyethylene films having improved mechanical and optical properties and at the same time a low seal initiation temperature (SIT) can be provided by using recycled polyethylene as a component of a core layer composition forming the core layer of the multilayer polyethylene film.

[0019] It has also been surprisingly found that large amounts, ie up to 95 wt. %, of recycled polyethylene can be used in the core layer composition without degrading the mechanical and optical properties of the multilayer polyethylene film.

[0020] In addition to using a large amount of recycled polyethylene in the core layer composition of the multilayer polyethylene film according to the present invention, the other polymer components used for the film layer are also polyethylene-based materials. In other words, the multilayer polyethylene film according to the present invention is based on or formed of polyethylene-based materials, that is, the multilayer film of the present invention is intended to achieve a single material solution based on polyethylene. Therefore, the multilayer polyethylene film according to the present invention has a dual advantage: the multilayer film is structurally made of a single material polyethylene, and its core layer can use a large amount of recycled polyethylene. Therefore, the multilayer polyethylene film of the present invention is designed for recycling.

[0021] The multilayer film according to the present invention has at least three layers, namely a skin layer, a sealing layer and a core layer located between the skin layer and the sealing layer. Typically, the multilayer polyethylene film according to the present invention has no more than 7 layers, preferably no more than 5 layers.

[0022] Preferably, the multilayer polyethylene film according to the present invention has three layers or consists of three layers, i.e., as described herein, the multilayer polyethylene film according to the present invention consists of a surface layer, a sealing layer and a core layer located between the surface layer and the sealing layer. In other words, the multilayer polyethylene film according to the present invention is preferably a three-layer polyethylene film.

[0023] Alternatively, the multilayer polyethylene film according to the present invention preferably also includes other layers except the skin layer, seal layer and core layer as described herein. If present, the other layers are located between the skin layer and the core layer and / or between the seal layer and the core layer. Preferably, the other layers are composed of a polyethylene-based composition.

[0024] Preferably, the skin layer and the seal layer are the outermost layers of the multilayer polyethylene film.

[0025] Core layer

[0026] The core layer comprises or consists of a core layer composition. The core layer composition comprises recycled polyethylene a) as a main component.

[0027] For the purposes of this specification and the subsequent claims, the term "recycled polyethylene" means a polymer material which, apart from other polymer components of any nature, comprises primarily units derived from ethylene. For example, such polymer components may be derived from monomer units derived from alpha olefins (e.g. propylene, butene, hexene, octene, etc.), styrene derivatives (e.g. vinyl styrene), substituted and unsubstituted acrylic acid esters, substituted and unsubstituted methacrylic acid esters.

[0028] The polymer material can be quantitatively 13 C{1H}NMR measurements were performed to identify the presence of polyethylene in mixed plastic compositions. 13 In C{1H}NMR measurements, and in the quantitative determinations described in the measurement methods below 13 In C{1H}NMR measurements, the different units in the polymer chain can be distinguished and quantified. These units are ethylene units (C2 units), units with 3, 4 and 6 carbon atoms, and units with 7 carbon atoms.

[0029] Therefore, the unit having 3 carbon atoms (C3 unit) can be distinguished in the NMR spectrum as an isolated C3 unit (isolated C3 unit) and continuous C3 units (continuous C3 unit), which indicates that the polymer material contains a propylene-based polymer. These continuous C3 units can also be identified as iPP units.

[0030] Units with 3, 4, 6 and 7 carbon atoms describe in the NMR spectrum units originating from two carbon atoms in the polymer backbone and short side chains or branches of 1 carbon atom (isolated C3 unit), 2 carbon atoms (C4 unit), 4 carbon atoms (C6 unit) or 5 carbon atoms (C7 unit).

[0031] The units with 3, 4 and 6 carbon atoms (isolated C3, C4 and C6 units) can originate from incorporated comonomers (propylene, 1-butene and 1-hexene comonomers) or from short chain branches formed by free radical polymerization.

[0032] Units with 7 carbon atoms (C7 units) can be clearly attributed to recycled polyethylene, since they cannot come from any comonomer. 1-Heptene monomer is not used for copolymerization. Instead, C7 units represent the presence of LDPE that is unique to recycled materials. It has been found that the amount of C7 units in LDPE resins is always within different ranges. Therefore, by quantitative 13 The amount of C7 units determined by C{1H} NMR measurement can be used to calculate the amount of LDPE in the polyethylene composition.

[0033] Therefore, the amount of continuous C3 unit, isolated C3 unit, C4 unit, C6 unit and C7 unit is determined by the quantitative method described below. 13 The LDPE content is measured by C{1H}NMR measurement, while the LDPE content is calculated based on the amount of C7 units as described below.

[0034] The total amount of ethylene units (C2 units) is due, besides the units of LDPE, ie the units with longer side chain branches of 6 or more carbon atoms, also to units in the polymer chain which do not have short side chains of 1 to 5 carbon atoms.

[0035] Preferably, the recycled polyethylene has an MFR2 of 0.5 to 1.5 g / 10 min measured according to ISO 1133 and a density of 915 to 930 kg / m 3 .

[0036] The total amount of ethylene units (C2 units) in the recovered polyethylene is preferably 80.0 to 96.0 wt %, more preferably 82.5 to 95.5 wt %, even more preferably 85.0 to 95.5 wt %, and most preferably 87.5 to 95.0 wt %, as measured by NMR of the d2-tetrachloroethylene soluble fraction, wherein the total amount of C2 units is based on the total weight of the monomer units in the recovered polyethylene and is calculated according to the quantitative 13 It was measured by C{1H}NMR measurement.

[0037] The total amount of continuous units with 3 carbon atoms (continuous C3 units) corresponding to polypropylene in the recycled polyethylene is preferably 0.2 to 6.5 wt%, more preferably 0.4 to 6.0 wt%, even more preferably 0.6 to 5.5 wt%, and most preferably 0.75 to 5.0 wt%; the total amount of continuous C3 units is based on the total weight of the monomer units in the recycled polyethylene and is calculated according to the quantitative 13 It was measured by C{1H}NMR measurement.

[0038] The total amount of units with a carbon number of 3 that are isolated C3 units (isolated C3 units) in the recycled polyethylene is preferably 0.00 wt% to 0.50 wt%, more preferably 0.00 wt% to 0.40 wt%, even more preferably 0.00 wt% to 0.30 wt%, and most preferably 0.00 wt% to 0.25 wt%;

[0039] The total amount of units having 4 carbon atoms (C4 units) is preferably 0.50 to 5.00% by weight, more preferably 0.75 to 4.00% by weight, still more preferably 1.00 to 3.50% by weight, most preferably 1.25 to 3.00% by weight;

[0040] The total amount of units having 6 carbon atoms (C6 units) is preferably 0.50 to 7.50% by weight, more preferably 0.75 to 6.50% by weight, still more preferably 1.00 to 5.50% by weight, most preferably 1.25 to 5.00% by weight;

[0041] The total amount of units having 7 carbon atoms (C7 units) is preferably 0.20 to 2.50% by weight, more preferably 0.30 to 2.00% by weight, still more preferably 0.40 to 1.50% by weight, most preferably 0.45 to 1.25% by weight, and

[0042] The LDPE content is preferably 20.0 wt% to 65.0 wt%, more preferably 25.0 wt% to 62.5 wt%, even more preferably 30.0 wt% to 60.0 wt%, most preferably 32.0 wt% to 55.0 wt%.

[0043] The total amount of C2 units, continuous C3 units, isolated C3 units, C4 units, C6 units, C7 units and LDPE content is based on the total weight of monomer units in the recycled polyethylene and is quantitatively determined based on the total weight of the monomer units in the recycled polyethylene. 13 C{1H}NMR measurement is measured or calculated.

[0044] Preferably, the total amount of units attributable to the comonomers (i.e., isolated C3 units, C4 units, and C6 units) in the recycled polyethylene is from 4.00 to 20.00 wt%, more preferably from 4.50 to 17.50 wt%, even more preferably from 4.75 to 15.00 wt%, most preferably from 5.00 to 12.50 wt%, and according to the quantitative 13 C{1H}NMR measurement was performed.

[0045] The recycled polyethylene preferably does not contain carbon black. It is further preferred that the recycled polyethylene does not contain any pigments other than carbon black.

[0046] Recycled polyethylene may also include:

[0047] 0 to 10 wt% of units derived from alpha olefins, 0 to 3.0 wt% of stabilizers, 0 to 3.0 wt% of talc, 0 to 3.0 wt% of chalk, 0 to 6.0 wt% of other components, all percentages relative to the recycled polyethylene.

[0048] The recycled polyethylene preferably has one or more, more preferably all, of the following properties in any combination:

[0049] MFR5 (ISO 1133, 5.0 kg, 190°C) is 1.5 to 5.0 g / 10 min, more preferably 2.0 to 4.0 g / 10 min;

[0050] MFR 21(ISO 1133, 21.6 kg, 190 ° C) is 20.0 to 50.0 g / 10 min, more preferably 25.0 to 45.0 g / 10 min;

[0051] Polydispersity index PI is 1.0 to 3.5s -1 , more preferably 1.3 to 3.0s -1 ;

[0052] Shear Thinning Index SHI 2.7 / 210 15 to 40, more preferably 20 to 35;

[0053] The complex viscosity eta300 at a frequency of 300 rad / s is 500 to 750 Pa·s, more preferably 550 to 700 Pa·s;

[0054] The complex viscosity eta0.05 at a frequency of 0.05 rad / s is 15000 to 30000 Pa·s, more preferably 15500 to 27500 Pa·s;

[0055] The strain hardening modulus SH modulus is 12.5 to 20.0 MPa, more preferably 13.0 to 17.5 MPa.

[0056] Preferably, the recycled polyethylene has a relatively low gel content, especially compared to other mixed plastic polyethylene recycled blends.

[0057] For gels with a size of 600 μm or more to 1000 μm, the gel content of the recycled polyethylene is preferably not more than 1000 gels / m 2 , more preferably not more than 850 gel / m 2 For gels with a size of 600 μm or more to 1000 μm, the lower limit of gel content is usually 100 gels / m 2 , preferably 150 gel / m 2 .

[0058] Furthermore, for gels with a size exceeding 1000 μm, the gel content of the mixed plastic polyethylene composition is preferably not more than 200 gels / m 2 , more preferably not more than 150 gel / m 2 For gels larger than 1000 μm, the lower limit of gel content is usually 10 gels / m 2 , preferably 14 gel / m 2 .

[0059] The recycled polyethylene is preferably present in the core layer composition in an amount of 50 to 95 wt%, more preferably 55 to 90 wt%, more preferably 60 to 85 wt%, more preferably 65 to 75 wt%, based on the total core layer composition.

[0060] The core layer composition further comprises b) a multimodal ethylene terpolymer.

[0061] Typically, ethylene polymers can be unimodal or multimodal, e.g., bimodal. As used herein, the "modality" of a polymer refers to the structure of the molecular weight distribution of the polymer, i.e., the appearance of a curve representing the number of molecules as a function of molecular weight. If the curve shows a single maximum, the polymer is referred to as "unimodal", while if the curve shows a very wide maximum or two or more maxima and the polymer consists of two or more fractions, the polymer is referred to as "bimodal", "multimodal", etc. For example, if a polymer is produced in a sequential multi-stage process using reactors connected in series and using different conditions in each reactor, the polymer fractions produced in the different reactors will each have their own molecular weight distribution and weight average molecular weight. When the molecular weight distribution curve of such a polymer is recorded, the individual curves of these fractions are superimposed into the molecular weight distribution curve of the total resulting polymer product, typically resulting in a curve with two or more different maxima.

[0062] In the production of unimodal ethylene polymers, ethylene polymers are produced in a reactor under specific conditions, including monomer composition, hydrogen pressure, temperature, pressure, etc. In the copolymerization of ethylene, other olefins having up to 12 carbon atoms are usually used as comonomers, for example, α-olefins having 3 to 12 carbon atoms, such as propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, etc.

[0063] For example, in the production of bimodal ethylene polymers, a first ethylene polymer is produced in a first reactor under specific conditions, including monomer composition, hydrogen pressure, temperature, pressure, etc. After polymerization in the first reactor, the reaction mixture including the resulting polymer is fed to a second reactor, where further polymerization is carried out under other conditions. Typically, a first polymer of high melt flow rate (low molecular weight) is produced in the first reactor, with an appropriate or small amount of comonomer added, or no comonomer added at all, while a second polymer of low melt flow rate (high molecular weight) is produced in the second reactor, with more comonomer added. The resulting final product consists of an intimate mixture of polymers from the two reactors, the different molecular weight distribution curves of these polymers together forming a molecular weight distribution curve with a broad maximum or two maxima, i.e., the final product is a bimodal polymer mixture.

[0064] The multimodal ethylene terpolymer b) preferably comprises or consists of a copolymer of ethylene and at least two different α-olefin comonomers having 4 to 10 carbon atoms, the copolymer consisting of:

[0065] (i) 30.0 to 70.0 wt% of an ethylene polymer component (A) having a density of 920 to 950 kg / m 3 , MFR2 measured according to ISO 1133 is from 2.0 to 40.0 g / 10 min; and

[0066] (ii) 70.0 to 30.0 wt% of an ethylene polymer component (B) having a density of 880 to 915 kg / m 3 , MFR2 measured according to ISO 1133 is 0.01 to 1.5 g / 10 min;

[0067] or

[0068] (i) 30.0 to 70.0 wt.% of an ethylene polymer fraction (A-1) and an ethylene polymer fraction (A-2), wherein the ethylene polymer fraction (A-1) has a density of 920 to 960 kg / m 3 , MFR2 measured according to ISO 1133 is from 1.0 to 50.0 g / 10 min, and wherein the ethylene polymer fraction (A-2) has a density measured according to ISO 1183 of from 930 to 950 kg / m 3 , MFR2 measured according to ISO 1133 is from 3.0 to 60.0 g / 10 min; wherein the ratio of the MFR2 of the ethylene polymer fraction (A-1) to the MFR2 of the ethylene polymer component (A) is greater than 0.3; and

[0069] (ii) 70.0 to 30.0 wt% of an ethylene polymer component (B) having a density of 880 to 915 kg / m 3 , MFR2 measured according to ISO 1133 is 0.01 to 1.5 g / 10 min.

[0070] The MFR2 of the ethylene polymer component (A) measured according to ISO 1133 is preferably from 2.0 to 40 g / 10 min, preferably from 2.5 to 30 g / 10 min, more preferably from 3.0 to 20 g / 10 min, even more preferably from 3.2 to 10 g / 10 min.

[0071] The MFR2 of the ethylene polymer fraction (A-1) measured according to ISO 1133 is preferably 1.0 to 50.0 g / 10 min, more preferably 1.5 to 40.0 g / 10 min, more preferably 2.0 to 30.0 g / 10 min and even more preferably 2.5 to 20.0 g / 10 min, most preferably 3.0 to 10.0 g / 10 min.

[0072] The ethylene polymer fraction (A-2) has a higher MFR2 than the ethylene polymer fraction (A-1), i.e. the MFR2 of the ethylene polymer fraction (A-2) measured according to ISO 1133 is from 3.0 to 60.0 g / 10 min, preferably from 3.2 to 30.0 g / 10 min, more preferably from 3.5 to 20.0 g / 10 min, and most preferably from 3.5 to 15.0 g / 10 min.

[0073] The MFR2 of the ethylene polymer component (B) measured according to ISO 1133 is preferably from 0.01 to 1.5 g / 10 min, preferably from 0.05 to 1.5 g / 10 min, more preferably from 0.1 to 1.3 g / 10 min, even more preferably from 0.2 to 1.2 g / 10 min.

[0074] Furthermore, the ratio of the MFR2 of the ethylene polymer fraction (A-1) to the MFR2 of the ethylene polymer component (A) is preferably greater than 0.3, preferably in the range of 0.50 to 1.0, more preferably in the range of 0.60 to 1.0, even more preferably in the range of 0.70 to 1.0, for example 0.80 to 0.98.

[0075] Furthermore, the ratio of the MFR2 of the ethylene polymer component (A) to the MFR2 of the final multimodal ethylene terpolymer b) is greater than 2.1, preferably from 2.3 to 12.0, more preferably from 2.5 to 10.0, even more preferably from 2.8 to 8.0.

[0076] The at least two α-olefin comonomers having 4 to 10 carbon atoms of the multimodal ethylene terpolymer are preferably butene and hexene.

[0077] The α-olefin comonomers of the ethylene polymer component (A) and the ethylene polymer fractions (A-1) and (A-2) are preferably the same, so the component (A) and the fractions (A-1) and (A-2) use the same α-olefin comonomer having 4 to 10 carbon atoms, and more preferably the component (A) and the fractions (A-1) and (A-2) have 1-butene as the α-olefin comonomer. In other words, the ethylene polymer component (A) is an ethylene-1-butene copolymer, the ethylene polymer fraction (A-1) is an ethylene-1-butene copolymer, and the ethylene polymer fraction (A-2) is an ethylene-1-butene copolymer. Preferably, the ethylene polymer component (B) is an ethylene-1-hexene copolymer.

[0078] Most preferably, the ethylene polymer component (A) is an ethylene-1-butene copolymer and the ethylene polymer component (B) is an ethylene-1-hexene copolymer, or the ethylene polymer fraction (A-1) is an ethylene-1-butene copolymer, the ethylene polymer fraction (A-2) is an ethylene-1-butene copolymer and the ethylene polymer component (B) is an ethylene-1-hexene copolymer.

[0079] The α-olefin comonomer content of components (A) and (B) can be measured, or, in a preferred case, one of the components is produced first and then the other component is produced in the presence of the first produced component in a so-called multi-stage process, then the α-olefin comonomer content of the first produced component (e.g. component (A)) can be measured and the comonomer content of the other component (e.g. component (B)) can be calculated according to the following formula.

[0080] Comonomer content in component B (mol%) = (comonomer content in final product (mol%) - (weight fraction of component A * comonomer content in component A (mol%)) / (weight fraction of component B)

[0081] More preferably the total amount of α-olefin comonomer present in the multimodal ethylene terpolymer b) is from 0.5 to 10.0 mol-%, preferably from 1.0 to 8.0 mol-%, more preferably from 1.5 to 6.0 mol-%, more preferably from 2.0 to 5.0 mol-% based on the multimodal ethylene terpolymer.

[0082] The total amount of 1-butene based on the multimodal ethylene terpolymer is preferably in the range of 0.05 to 1.0 mol-%, preferably in the range of 0.10 to 0.8 mol-%, more preferably in the range of 0.15 to 0.5 mol-%.

[0083] The total amount of 1-hexene based on the multimodal ethylene terpolymer is preferably in the range of 0.45 to 9.0 mol-%, preferably in the range of 0.90 to 7.2 mol-%, more preferably in the range of 1.35 to 5.5 mol-%.

[0084] Preferably, the total amount (mol %) of α-olefin comonomers having 4 to 10 carbon atoms (preferably selected from butene, hexene and octene, especially butene) present in the ethylene polymer component (A) is from 0.05 to 5.0 mol %, more preferably from 0.1 to 4.0 mol %, even more preferably from 0.2 to 3.0 mol %, even more preferably from 0.3 to 2.0 mol %, and most preferably from 0.3 to 1.0 mol %, based on the ethylene polymer component (A).

[0085] In one embodiment, the amount (mol %) of the α-olefin comonomer having 6 to 10 carbon atoms, preferably selected from hexene and octene, especially hexene, present in the ethylene polymer component (B) is 2.5 to 10.0 mol %, preferably 3.0 to 9.0 mol %, more preferably 3.5 to 8.0 mol %, even more preferably 4.0 to 7.0 mol %, based on the ethylene polymer component (B).

[0086] Preferably, the density of the ethylene polymer component (A) is different from the density of the ethylene polymer component (B), preferably higher than the density of the ethylene polymer component (B).

[0087] The density of the ethylene polymer component (A) is in the range of 920 to 950 kg / m 3 In the range of 925 to 950 kg / m 3 , more preferably 930 to 945 kg / m 3 , and / or the density of the ethylene polymer component (B) is from 880 to 915 kg / m 3 In the range of 890 to 905 kg / m 3 .

[0088] The density of the polymer fraction (A-1) is between 920 and 960 kg / m 3 In the range of 925 to 955 kg / m 3 , more preferably 930 to 950 kg / m 3 , and most preferably 935 to 945 kg / m 3 .

[0089] The density of the polymer fraction (A-2) is between 930 and 950 kg / m 3 In the range of 935 to 945 kg / m 3 .

[0090] The ethylene polymer fractions (A-1) and (A-2) are preferably present in an amount of 30.0 to 70.0 wt%, preferably 32.0 to 55.0 wt%, even more preferably 34.0 to 45.0 wt%, based on the multimodal ethylene terpolymer. Preferably, the weight ratio of the first and second ethylene polymer fractions (A-1 and A-2) is preferably from 4:1 to 1:4, such as from 3:1 to 1:3, or from 2:1 to 1:2, or 1:1.

[0091] The ethylene polymer component (A) is preferably present in an amount of 30.0 to 70.0 wt%, preferably 32.0 to 55.0 wt%, even more preferably 34.0 to 45.0 wt%, based on the multimodal ethylene terpolymer.

[0092] Thus, the ethylene polymer fraction (B) is preferably present in an amount of 70.0 to 30.0 wt%, preferably 68.0 to 45.0 wt%, more preferably 66.0 to 55.0 wt%, based on the multimodal ethylene terpolymer.

[0093] The multimodal ethylene terpolymer preferably has an MFR2 of from 0.75 to 1.75 g / 10 min, measured according to ISO 1133, and / or preferably a density of from 914 to 922 kg / m 3 .

[0094] MFR of multimodal ethylene terpolymers determined according to ISO 1133 21 It is preferably 20 to 40 g / 10 min, more preferably 25 to 35 g / 10 min, and most preferably 28 to 32 g / 10 min.

[0095] The multimodal ethylene terpolymer is preferably a bimodal ethylene terpolymer.

[0096] The multimodal ethylene terpolymer is preferably a metallocene-catalyzed multimodal ethylene terpolymer. In other words, the multimodal ethylene terpolymer b) is obtained by a metallocene-catalyzed polymerization process. The metallocene-catalyzed multimodal ethylene terpolymer can be produced by a three-stage process, preferably comprising a first slurry reactor (loop reactor 1), wherein the first slurry loop reactor is connected in series with another slurry reactor (loop reactor 2), so that the first ethylene polymer fraction (A-1) produced in the loop reactor 1 is fed into the loop reactor 2, wherein the second ethylene polymer fraction (A-2) is produced in the presence of the first fraction (A-1). The loop reactor 2 is thus connected in series to a gas phase reactor (GPR) to produce the multimodal ethylene terpolymer c). In this case, the reaction conditions in the two slurry reactors are selected so that products with different MFR and / or density are produced in the two slurry reactors.

[0097] Such processes are described in particular in WO 2016 / 198273, WO 2021 / 009189, WO 2021 / 009190, WO 2021 / 009191 and WO 2021 / 009192. Full details on how to prepare suitable metallocene-catalyzed multimodal ethylene terpolymers can be found in these references.

[0098] A suitable process is the Borstar PE 3G process.

[0099] The multimodal ethylene terpolymer is preferably a linear low density polyethylene.The MWD of the bimodal or multimodal ethylene terpolymer is preferably from 3.0 to 5.0, more preferably from 3.5 to 4.5 and most preferably from 3.7 to 4.3, as determined by GPC (gel permeation chromatography).

[0100] The multimodal ethylene terpolymer is preferably present in the core layer composition in an amount of 5 to 30 wt%, more preferably 10 to 25 wt%, more preferably 15 to 20 wt%, based on the total core layer composition.

[0101] The core layer composition also includes c) polyethylene.

[0102] Preferably, the polyethylene is multimodal, preferably trimodal, and / or is a terpolymer.

[0103] More preferably, the polyethylene is a trimodal copolymer comprising or consisting of:

[0104] a) 10 to 30 wt % of a first ethylene homopolymer;

[0105] b) 15 to 35 wt% of a second ethylene homopolymer having an MFR2 at least 50 g / 10 min higher than the MFR2 of component a); and

[0106] c) 40 to 65 weight percent of a third ethylene copolymer having at least one α-olefin comonomer.

[0107] Even more preferably, the polyethylene is a trimodal terpolymer comprising or consisting of:

[0108] a) 10 to 30 wt % of a first ethylene homopolymer;

[0109] b) 15 to 35 wt% of a second ethylene homopolymer having an MFR2 at least 50 g / 10 min higher than the MFR2 of component a); and

[0110] c) 40 to 65 weight percent of a third ethylene terpolymer having at least two α-olefin comonomers.

[0111] Preferably, the third fraction c) of polyethylene c) is an ethylene 1-hexene copolymer or a terpolymer of ethylene and at least two α-olefin comonomers (e.g. 1-butene and 1-hexene), i.e. an ethylene-1-butene-1-hexene terpolymer. In other words, the third ethylene copolymer with at least one α-olefin comonomer is preferably an ethylene-1-hexene copolymer, or the third ethylene terpolymer with at least two α-olefin comonomers is preferably an ethylene-1-butene-1-hexene terpolymer.

[0112] Preferably, the total amount of α-olefin comonomers present in the polyethylene c) is 1.0 to 15.0 wt%, more preferably 2.0 to 10.0 wt%, more preferably 3.5 to 8.0 wt%, and most preferably 4.0 to 6.5 wt%, based on the total polyethylene.

[0113] If the polyethylene c) is a trimodal copolymer, wherein the third ethylene copolymer with at least one α-olefin comonomer is an ethylene-1-hexene copolymer, the total amount of 1-hexene is preferably from 1.0 to 10.0 wt.-%, more preferably from 2.0 to 7.0 wt.-%, more preferably from 3.0 to 5.0 wt.-%, and most preferably from 3.1 to 4.6 wt.-%, based on the total trimodal copolymer.

[0114] If the polyethylene c) is a trimodal terpolymer, wherein the third ethylene terpolymer with at least two α-olefin comonomers is an ethylene-1-butene-1-hexene terpolymer, the total amount of 1-butene is preferably from 0.1 to 5.0 wt.-%, more preferably from 0.4 to 4.0 wt.-%, more preferably from 0.7 to 3.0 wt.-%, more preferably from 0.9 to 2.5 wt.-%, and most preferably from 1.0 to 2.2 wt.-%, based on the total trimodal terpolymer and / or the total amount of 1-hexene is preferably from 1.0 to 10.0 wt.-%, more preferably from 2.0 to 7.0 wt.-%, more preferably from 3.0 to 5.0 wt.-%, and most preferably from 3.1 to 4.6 wt.-%, based on the total trimodal terpolymer.

[0115] Preferably, the polyethylene has an MFR2 measured according to ISO 1133 of from 0.2 to 0.5 g / 10 min.

[0116] Preferably, the polyethylene has an MFR5 of 1 to 2.0 g / 10 min, more preferably 1.25 to 1.75 g / 10 min, as measured according to ISO 1133, and a density of preferably 925 to 945 kg / m 3 , more preferably 930 to 945 kg / m 3 .

[0117] In addition to MFR5 and density, the MFR of polyethylene measured according to ISO 1133 21 It is preferably 25 to 45 g / 10 min, more preferably 30 to 40 g / 10 min, and most preferably 32 to 38 g / 10 min.

[0118] FRR of Polyethylene 21 / 5 Preferably it is in the range of 18 to 28.

[0119] The polyethylene is preferably a Ziegler-Natta catalyzed polyethylene. In other words, the polyethylene c) is obtained by a Ziegler-Natta catalyzed polymerization process. The MWD of the polyethylene is preferably from 10 to 30, more preferably from 15 to 25, and most preferably from 19 to 22, as determined by GPC (gel permeation chromatography).

[0120] The content of polyethylene in the core layer composition is preferably 5 to 30 wt%, more preferably 6 to 25 wt%, more preferably 8 to 15 wt%, based on the total core layer composition.

[0121] surface layer

[0122] The multilayer polyethylene film of the present invention further comprises a surface layer, which is preferably the outermost layer of the multilayer polyethylene film.

[0123] Preferably, the skin layer comprises or consists of a skin layer composition comprising or consisting of a multimodal ethylene terpolymer and / or a low density polyethylene, the multimodal ethylene terpolymer having an MFR2 of 0.5 to 2.0 g / 10 min, preferably 0.75 to 1.75 g / 10 min, measured according to ISO 1133, and a MFR of 910 to 930 kg / m 3 , preferably 914 to 922 kg / m 3 The low density polyethylene has a density of 0.1 to 2.0 g / 10 min, preferably 0.5 to 1.25 g / 10 min, and a MWD of 2.0 to 7.5 as determined by GPC (gel permeation chromatography), the low density polyethylene having an MFR2 of 0.1 to 2.0 g / 10 min, preferably 0.5 to 1.25 g / 10 min, as determined according to ISO 1133, and a MFR of 910 to 950 kg / m 3 , preferably 915 to 930 kg / m 3 , more preferably 918 to 927 kg / m 3 The multimodal ethylene terpolymer of the skin layer is preferably the same as the multimodal ethylene terpolymer of the core layer, as described in all embodiments herein.

[0124] More preferably, the skin layer comprises a skin layer composition comprising a multimodal ethylene terpolymer as defined in all embodiments herein and a low density polyethylene as defined in all embodiments herein.

[0125] MFR of low density polyethylene measured according to ISO 1133 21 It is preferably 48 to 68 g / 10 min, more preferably 53 to 63 g / 10 min, and most preferably 56 to 60 g / 10 min.

[0126] The low density polyethylene preferably has a MWD of 4.0 to 9.0, more preferably 5.0 to 8.0, and most preferably 6.0 to 7.4 as determined by GPC (gel permeation chromatography). The low density polyethylene is preferably a high pressure tubular LDPE. In other words, the LDPE is produced in a tubular reactor under high pressure conditions, typically 100 to 400 MPa.

[0127] The multimodal ethylene terpolymer is preferably present in the skin layer composition in an amount of 80 to 95 wt%, more preferably 85 to 93 wt%, based on the total skin layer composition.

[0128] The low density polyethylene is preferably present in the skin layer composition in an amount of 5 to 20 wt%, more preferably 5 to 20 wt%, more preferably 7 to 15 wt%, based on the total skin layer composition.

[0129] Sealing layer

[0130] The multi-layer polyethylene film of the present invention further comprises a sealing layer, and the sealing layer is preferably the outermost layer of the multi-layer polyethylene film.

[0131] Preferably, the sealing layer comprises or consists of a sealing layer composition comprising or consisting of a copolymer and / or a multimodal ethylene terpolymer of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms, wherein the copolymer of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms has an MFR2 of 0.5 to 2.0 g / 10 min, preferably 0.75 to 1.25 g / 10 min, measured according to ISO 1133, and a density of 870 to 910 kg / m 3 , preferably 890 to 910 kg / m 3 The multimodal ethylene terpolymer has an MFR2 of 0.5 to 2.0 g / 10 min, measured according to ISO 1133, and a density of 910 to 930 kg / m 3 As described in all embodiments herein, the multimodal ethylene terpolymer of the sealant layer is preferably the same as the multimodal ethylene terpolymer of the core layer.

[0132] More preferably, the sealant layer comprises a sealant layer composition comprising a copolymer of ethylene and an alpha-olefin having 4 to 8 carbon atoms as defined herein and a multimodal ethylene terpolymer as defined herein in all embodiments.

[0133] The α-olefin comonomer having 4 to 8 carbon atoms is preferably 1-octene. In other words, the copolymer of ethylene and the α-olefin comonomer having 4 to 8 carbon atoms is preferably an ethylene-1-octene copolymer.

[0134] The α-olefin comonomer of the copolymer is preferably present in an amount of 10 to 30 wt%, more preferably 12 to 24 wt%, and most preferably 14 to 18 wt%, based on the total copolymer of ethylene and α-olefin comonomer having 3 to 8 carbon atoms.

[0135] MFR of copolymers of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms, determined according to ISO 1133 21 It is preferably 28 to 48 g / 10 min, more preferably 33 to 43 g / 10 min, and most preferably 36 to 40 g / 10 min.

[0136] The copolymer of ethylene and an alpha-olefin comonomer having 4 to 8 carbon atoms is preferably a metallocene-catalyzed copolymer of ethylene and an alpha-olefin comonomer having 4 to 8 carbon atoms. In other words, the copolymer of ethylene and an alpha-olefin comonomer having 4 to 8 carbon atoms is obtained by a metallocene-catalyzed polymerization process. The MWD of the copolymer of ethylene and an alpha-olefin comonomer having 4 to 8 carbon atoms is preferably 2.0 to 4.0, more preferably 2.5 to 3.5, and most preferably 2.7 to 3.3 as determined by GPC (gel permeation chromatography).

[0137] The copolymer of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms is preferably present in the sealant layer composition in an amount of 50 to 90 wt%, more preferably 55 to 80 wt%, more preferably 55 to 65 wt%, based on the total sealant layer composition.

[0138] The multimodal ethylene terpolymer is preferably present in the sealant layer composition in an amount of 10 to 50 wt%, more preferably 20 to 45 wt%, more preferably 35 to 45 wt%, based on the total sealant layer composition.

[0139] Each layer of the multilayer polyethylene film according to the present invention has a certain thickness.

[0140] The thickness of the surface layer is preferably 1 to 100 μm, more preferably 5 to 50 μm, and most preferably 10 to 20 μm.

[0141] The thickness of the core layer is preferably 10 to 200 μm, more preferably 20 to 100 μm, and most preferably 30 to 50 μm.

[0142] The thickness of the sealing layer is preferably 1 to 50 μm, more preferably 5 to 50 μm, and most preferably 10 to 20 μm.

[0143] The thickness of the multilayer polyethylene film according to the present invention is preferably from 12 to 350 μm, more preferably from 30 to 200 μm, and most preferably from 50 to 90 μm.

[0144] The multilayer polyethylene film preferably has a tensile modulus in the longitudinal direction (MD) measured on a 60 μm test film according to ISO527-3 of at least 150 MPa, more preferably at least 200 MPa, and / or a tensile modulus in the transverse direction (TD) measured on a 60 μm test film according to ISO527-3 of at least 150 MPa, preferably at least 200 MPa.

[0145] Typically, the multilayer polyethylene film has a longitudinal (MD) tensile modulus of not more than 1000 MPa, preferably not more than 800 MPa, more preferably not more than 600 MPa, measured on a 60 μm test film according to ISO 527-3, and / or a transverse (TD) tensile modulus of not more than 1000 MPa, preferably not more than 800 MPa, more preferably not more than 600 MPa, measured on a 60 μm test film according to ISO 527-3.

[0146] The multilayer polyethylene film preferably has a dart impact strength (DDI) of greater than 300 g, more preferably greater than 350 g, and most preferably greater than 375 g, measured according to ISO 7765 on a 60 μm test film, and / or a SIT (seal initiation temperature) of less than 82° C., more preferably less than 80° C., and most preferably less than 78° C. The SIT is determined as described herein.

[0147] Typically, the multilayer polyethylene film has a dart drop impact strength (DDI) of not more than 2000 g, preferably not more than 1500 g, more preferably not more than 1000 g, measured on a 60 μm test film according to ISO 7765, and / or a SIT (seal initiation temperature) of greater than 70° C., more preferably greater than 74° C., and most preferably greater than 76° C. The SIT is determined as described herein.

[0148] The multilayer polyethylene film of the present invention is preferably a blown film.

[0149] The present invention also provides a process for producing a multilayer polyethylene film according to the present invention, wherein the skin layer, the seal layer and the core layer are coextruded.

[0150] The different polymer components in any layer of the multilayer polyethylene film are usually intimately mixed before the layer is formed, for example using a twin screw extruder, preferably a counter-rotating extruder. The blend is then converted into a coextruded film structure. Preferably, the blend is converted into a coextruded film structure on a blown film production line.

[0151] To make such a multilayer polyethylene film according to the invention, typically at least two polymer melt streams are simultaneously extruded (i.e. co-extruded) through a multi-channel tubular, annular or circular die to form a tube which is blown, inflated and / or cooled with air (or a combination of gases) to form a film. The manufacture of blown film is a well-known process.

[0152] Blown coextrusion may be carried out at a temperature of 160°C to 240°C and cooled by blowing (usually air) at a temperature of 10°C to 50°C to provide a frost line height of 1 to 8 times the die diameter.

[0153] The blow up ratio (BUR) should generally be in the range of 1.2 to 6, preferably 1.5 to 4.

[0154] All preferred embodiments of the multilayer polyethylene film according to the invention are also preferred embodiments of the method for producing the multilayer polyethylene film.

[0155] The present invention also provides a core layer composition, which comprises

[0156] a) recycled polyethylene having an MFR2 of 0.1 to 2.0 g / 10 min, preferably 0.5 to 1.5 g / 10 min, measured according to ISO 1133, and a density of 910 to 930 g / 10 min, measured according to ISO 1183;

[0157] kg / m 3 , preferably 915 to 930 kg / m 3 ,

[0158] b) a multimodal ethylene terpolymer having an MFR2 determined according to ISO 1133 of from 0.5 to 2.0

[0159] g / 10min, density determined according to ISO 1183 is 910 to 930 kg / m 3 , and the MWD determined by GPC (gel permeation chromatography) is 2.0 to 7.5,

[0160] c) polyethylene having an MFR5 of 0.1 to 2.5 g / 10 min, preferably 1 to 2.0 g / 10 min, measured according to ISO 1133, and a density of 925 to 950 kg / m 3 , preferably 935 to 945 kg / m 3 , and the MWD determined by GPC (gel permeation chromatography) is 8.0 to 35.0.

[0161] All preferred embodiments of the core layer composition for the multilayer polyethylene film according to the present invention are also preferred embodiments of the core layer composition according to the present invention. In addition, all preferred embodiments of the recycled polyethylene, multimodal ethylene terpolymer and polyethylene defined above are also preferred embodiments of the core layer composition according to the present invention.

[0162] The present invention also relates to the use of the core layer composition as a core layer of a multilayer film to improve the haze and SIT of the multilayer film.

[0163] All preferred embodiments described above for the core layer composition for the multilayer polyethylene film according to the invention and for the core layer composition according to the invention are also preferred embodiments of the use according to the invention.

[0164] Finally, the present invention provides an article comprising the multilayer polyethylene film according to the present invention or the core layer composition according to the present invention. Preferably, the article is a bag, such as a stand-up bag, a sack, a bag, a pouch. DETAILED DESCRIPTION

[0165] Measurement and determination methods

[0166] Unless otherwise defined, the following definitions of terms and determination methods apply to the above general description of the invention as well as to the following examples.

[0167] a) Measurement of melt flow rate (MFR)

[0168] Melt flow rate (MFR) is measured according to ISO 1133 and is expressed in g / 10 min. The higher the melt flow rate, the lower the viscosity of the polymer. For polyethylene, at 190°C, the load is 2.16 kg (MFR2), 5.00 kg (MFR5) or 21.6 kg (MFR 21 ) was used to determine the MFR.

[0169] The FRR (flow rate ratio) is an indicator of molecular weight distribution and represents the flow rate ratio under different loads. 21 / 5 Indicates MFR 21 / MFR5 value.

[0170] b) Density

[0171] The density of the polymer is measured in kg / m according to ISO 1183-1:2004 (method A) on compression molded specimens prepared according to ISO 17855-2. 3 .

[0172] The density of the polymer blend is calculated as follows. The density of the blend d b The calculation is as follows

[0173]

[0174] where wi and di are the weight percent and density of fraction i in the polymer blend.

[0175] c) Comonomer content

[0176] The comonomer content was determined as described in WO 2019081611, pages 31 to 34.

[0177] d) Mechanical properties

[0178] Tensile modulus

[0179] Film tensile properties were determined at 23° C. according to ISO 527-3 using blown film specimen type 2 as shown below. The machine direction (MD) tensile modulus and transverse direction (TD) tensile modulus, i.e., 1% secant modulus, were determined according to ASTM D882 at a test speed of 5 mm / min and a gauge length of 50 mm.

[0180] Film samples were produced as described below in "Examples".

[0181] Dart impact strength

[0182] DDI is measured in accordance with ISO 7765-1:1988 / Method A on films having the thickness indicated in the Examples and produced as described in the Examples below. This test method covers the determination of the energy required to rupture a film by impacting it with a free-falling dart from a specified height under specified conditions, which will cause rupture in 50% of the test specimens (Step Method A). Uniform increments of missile mass are used during the test, and depending on the observed results (rupture or non-rupture) for the specimen, the missile weight is reduced or increased by uniform increments after each specimen is tested.

[0183] Standard conditions:

[0184] Adjustment time: >96 hours

[0185] Test temperature: 23℃

[0186] Dart head material: phenolic resin

[0187] Dart diameter: 38mm

[0188] Drop height: 660mm

[0189] result:

[0190] Impact failure weight - 50% [g]

[0191] e) Optical properties

[0192] Haze is a measure of the optical appearance of a film and is determined according to ASTM D1003 on films having the thickness indicated in and produced as described in the Examples below.

[0193] f) Sealing Initiation Temperature (SIT)

[0194] This method determines the sealing temperature range (sealing range) of polyethylene films, in particular blown films or cast films. The sealing temperature range is the temperature range over which the film can be sealed according to the conditions given below.

[0195] The lower limit (seal initiation temperature (SIT)) is the sealing temperature when the seal strength reaches 5 N. The upper limit (seal end temperature (SET)) is reached when the film sticks to the sealing device.

[0196] The measurements were performed according to a slightly modified ASTM F1921-12, where the test parameters sealing pressure, cooling time and test speed were modified. The force / temperature curve was determined until thermal failure of the film.

[0197] The sealing range was determined by a J&B Universal Sealer Model 4000 using a film produced as follows, a blown film with a thickness of 60 μm as shown below, with the following further parameters:

[0198] Adjustment time: >96 hours

[0199] Sample width: 25mm

[0200] Sealing pressure: 0.4N / mm2(PE)

[0201] Sealing time: 1 second

[0202] Delay time: 30 seconds

[0203] Sealing jaw size: 50x5 mm

[0204] Sealing jaw shape: flat

[0205] Sealing jaw coating: Niptef

[0206] Sealing temperature: ambient temperature -240℃

[0207] Sealing temperature interval: 5°C

[0208] Starting temperature: 50℃

[0209] Clamping separation rate: 42mm / sec

[0210] g) Thickness

[0211] Film thickness is measured according to ISO 4593.

[0212] h) Quantification of C2, iPP (continuous C3), LDPE and polyethylene short chain branches in polyethylene-based recycled materials

[0213] Quantitative measurements were recorded in solution using a Bruker AvanceIII 400 MHz NMR spectrometer. 13C{ 1 H}NMR spectrum, 1 H and 13 C operated at 400.15 and 100.62 MHz, respectively. All spectra were acquired using 13 C optimized 10 mm extended temperature probe head was recorded at 125 °C, and nitrogen was used for all pneumatics. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium-(III)-acetylacetonate (Cr(acac)3) to give a 65 mM solution of the relaxant in the solvent {singh09}. To ensure a homogeneous solution, the NMR tube was further heated in a rotating oven for at least 1 h after initial sample preparation in a heating block. After the tube was inserted into the magnet, it was rotated at 10 Hz. This setup was chosen primarily because of its high resolution and is required for accurate quantification of ethylene content. Standard single pulse excitation without NOE was employed, using an optimized tip angle, a 1 s recycle delay, and a two-stage WALTZ16 decoupling scheme {zhou07,busico07}. A total of 6144 (6k) transients were acquired for each spectrum.

[0214] Processing, integration and quantification using a proprietary computer program 13 C{1H}NMR spectra were obtained and relevant quantitative properties were determined from the integration. All chemical shifts were indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. Characteristic signals corresponding to polyethylene (B1, B2, B4, B5, B6plus) and polypropylene with different short chain branches were observed {randall89, brandolini00}.

[0215] Characteristic signals corresponding to the presence of polyethylene containing isolated B1 branches (starB1 33.3ppm), isolated B2 branches (starB239.8ppm), isolated B4 branches (twoB4 23.4ppm), isolated B5 branches (threeB5 32.8ppm), all branches longer than 4 carbons (starB4plus 38.3ppm), and the third carbon at the end of the saturated fatty chain (3s 32.2ppm) were observed. The intensity of the ethylene backbone methine carbons (ddg) containing a combination of polyethylene backbone carbons (dd 30.0ppm), γ-carbons (g 29.6ppm) 4s and threeB4 carbons (which will be compensated later) was taken between 30.9ppm and 29.3ppm, excluding Tββ in polypropylene. All of the above signals were used to quantify the amount of C2 related carbons according to the following formula:

[0216] f C2total=(Iddg–ItwoB4)+(IstarB1*6)+(IstarB2*7)+(ItwoB4*9)+I(threeB5*10)+((IstarB4plus-ItwoB4-IthreeB5)*7)+(I3s*3)

[0217] Characteristic signals corresponding to the presence of polypropylene (iPP, continuous C3) were observed at 46.7 ppm, 29.0 ppm and 22.0 ppm. The amount of PP-related carbon was quantified using the Sαα integral at 46.6 ppm:

[0218] f PP =Isαα*3

[0219] The weight percentages of C2 fraction and polypropylene can be quantified according to the following formula:

[0220] wt C2fraction =fC C2total *100 / (fC C2total +fC PP )

[0221] wt PP =fC PP *100 / (fC C2total +fC PP )

[0222] Characteristic signals corresponding to the various short chain branches are observed and their weight percentages are quantified. Since the relevant branches will be α-olefins, first quantify the weight fraction of each branch:

[0223] fwtC2=fC C2total –((IstarB1*3)–(IstarB2*4)–(ItwoB4*6)–(IthreeB5*7)

[0224] fwtC3(isolated C3)=IstarB1*3

[0225] fwtC4=IstarB2*4

[0226] fwtC6=ItwoB4*6

[0227] fwtC7=IthreeB5*7

[0228] Normalization of all weight fractions yields the quantity of weight percentages of all relevant branches:

[0229] fsum wt%total =fwtC2+fwtC3+fwtC4+fwtC6+fwtC7+fC PP

[0230] wtC2total=fwtC2*100 / fsum wt%total

[0231] wtC3total=fwtC3*100 / fsum wt%total

[0232] wtC4total=fwtC4*100 / fsum wt%total

[0233] wtC6total=fwtC6*100 / fsum wt%total

[0234] wtC7total=fwtC7*100 / fsum wt%total

[0235] The LDPE content can be estimated by assuming that the B5 branches (generated solely by the polymerization of ethylene under high pressure processes) are almost constant in LDPE. We found that the average content of B5, if quantified as C7, is 1.46 wt%. Based on this assumption, a range of LDPE contents (roughly between 20 wt% and 80 wt%) can be estimated, depending on the SNR ratio of the three B5 signals:

[0236] wt%LDPE=wtC7total*100 / 1.46

[0237] References

[0238] zhou07 Zhou,Z.,Kuemmerle,R.,Qiu,X.,Redwine,D.,Cong,R.,Taha,A.,Baugh,D.Winniford,B.,J.Mag.Reson.187(2007)225

[0239] busico07 Busico,V.,Carbonniere,P.,Cipullo,R.,Pellecchia,R.,Severn,J.,Talarico,G.,Macromol.Rapid Commun.2007,28,1128

[0240] singh09 Singh,G.,Kothari,A.,Gupta,V.,Polymer Testing 28 5(2009),475

[0241] randall89 J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201.

[0242] brandolini00 AJ Brandolini, DDHills, NMR Spectra of Polymers and Polymer Additives, Marcel Dekker Inc., 2000

[0243] i) Dynamic shear measurement (frequency sweep measurement)

[0244] The characterization of the polymer composition or the melt of the polymer by dynamic shear measurement as given above or below complies with ISO standards 6721-1 and 6721-10. The measurements are carried out on an Anton Paar MCR501 stress-controlled rotational rheometer equipped with a 25 mm parallel plate geometry. The measurements are carried out on compression molded plates, using a nitrogen atmosphere and setting the strain in the linear viscoelastic range. The oscillatory shear tests are carried out at 190° C., applying a frequency range between 0.01 and 600 rad / s and setting a gap of 1.3 mm.

[0245] In dynamic shear experiments, the probe is subjected to uniform deformation under sinusoidally varying shear strain or shear stress (strain and stress controlled modes, respectively). In controlled strain experiments, the probe is subjected to a sinusoidal strain, which can be expressed as

[0246] γ(t)=γ0sin(ωt) (1)

[0247] If the applied strain is in the linear viscoelastic range, the resulting sinusoidal stress response can be given by:

[0248] σ(t)=σ0sin(ωt+δ) (2)

[0249] in

[0250] σ0 and γ0 are stress and strain amplitudes, respectively

[0251] ω is the angular frequency

[0252] δ is the phase shift (loss angle between applied strain and stress response)

[0253] t is time

[0254] Dynamic test results are usually expressed by several different rheological functions, namely shear storage modulus G', shear loss modulus G", complex shear modulus G*, complex shear viscosity η*, dynamic shear viscosity η', out-of-phase component of complex shear viscosity η", and loss tangent tanδ, which can be expressed as follows:

[0255]

[0256] G * =G′+iG″[Pa] (5)

[0257] η * =η′-iη″[Pa.s] (6)

[0258]

[0259] The so-called shear thinning index is related to MWD and is independent of Mw, and its determination is shown in Equation 9.

[0260]

[0261] For example, SHI (2.7 / 210) It is defined as the complex viscosity value (in Pas) determined when the G* value is equal to 2.7 kPa divided by the complex viscosity value (in Pas) determined when the G* value is equal to 210 kPa.

[0262] The values ​​of storage modulus (G′), loss modulus (G″), complex modulus (G*), and complex viscosity (η*) were obtained as a function of frequency (ω).

[0263] So, for example, η* 300rad / s (eta* 300rad / s ) is the abbreviation of complex viscosity at a frequency of 300 rad / s, η* 0.05rad / s (eta* 0.05rad / s ) is the abbreviation of complex viscosity at a frequency of 0.05 rad / s.

[0264] The loss tangent tan(δ) is defined as the ratio of the loss modulus (G″) to the storage modulus (G′) at a given frequency. Thus, for example, tan 0.05 It is the abbreviation of the ratio of loss modulus (G″) to storage modulus (G′) at 0.05 rad / s. 300 It is the abbreviation for the ratio of loss modulus (G″) to storage modulus (G′) at 300 rad / s.

[0265] Elastic balance tan 0.05 / tan 300 Defined as loss tangent tan 0.05 and loss tangent tan 300Ratio.

[0266] In addition to the above rheological functions, other rheological parameters can be determined, such as the so-called elastic index EI(x). The elastic index EI(x) is the value of the storage modulus (G') determined for a loss modulus (G") value of x kPa and can be described by Equation 10.

[0267] EI(x)=G′(G″=x kpa)[Pa] (10)

[0268] For example, EI(5 kPa) is defined by the value of the storage modulus (G'), determined by G" being equal to 5 kPa.

[0269] The polydispersity index PI is defined by Equation 11.

[0270]

[0271] where ω COP is the crossover angular frequency, determined as the angular frequency at which the storage modulus G′ is equal to the loss modulus G″.

[0272] These values ​​were determined by a single-point interpolation procedure defined in the Rheoplus software. In cases where a given G* value was not reached experimentally, the value was determined by extrapolation, using the same procedure as before. In both cases (interpolation or extrapolation), the options "Interpolate y-values ​​tox-values ​​from parameter" and "logarithmic interpolation type" in Rheoplus were applied.

[0273] References:

[0274] [1]Rheological characterization of polyethylene fractions” Heino, EL, Lehtinen, A., Tanner J., J.,Neste Oy,Porvoo,Finland,Theor.Appl.Rheol.,Proc.Int.Congr.Rheol,11th(1992),1,360-362

[0275] [2]The influence of molecular structure on some rheologicalproperties of polyethylene", Heino, EL, Borealis Polymers Oy, Porvoo, Finland, Annual Transactions of the Nordic Rheology Society, 1995.).

[0276] [3]Definition of terms relating to the non-ultimate mechanicalproperties of polymers,Pure&Appl.Chem.,Vol.70,No.3,pp.701-754,1998.

[0277] j) Strain hardening (SH) modulus

[0278] The strain hardening test is a modified tensile test performed at 80°C on specially prepared thin specimens. Strain Hardening Modulus (MPa) <gp>It is calculated from the true strain-true stress curve; the slope of the curve in the true strain λ region (between 8 and 12) is used.

[0279] The true strain λ is calculated based on the length l (mm) and the gauge length l0 (mm), as shown in Formula 1.

[0280]

[0281] Where Δl is the increase in the length of the specimen between gauge marks (mm). True stress σ true (MPa) Calculated according to Formula 2, assuming that the volume between the gauge marks is conserved:

[0282] σ true =σ n λ (2)

[0283] where σ n is the engineering stress.

[0284] The Neo-Hookean constitutive model (Equation 3) is used to fit the true strain-true stress data, from which the <gp>(MPa).

[0285]

[0286] where C is a mathematical parameter describing the constitutive model with the yield stress extrapolated to λ=0.

[0287] Initially measure five samples. If <gp>If the coefficient of variation is greater than 2.5%, measure two additional samples. If the test rod is strained in the clamp, discard the test result.

[0288] According to the pressing parameters specified in ISO 17855-2, the PE material granules were compression molded into sheets with a thickness of 0.30 mm.

[0289] After the sheet is compression molded, the sheet is annealed to eliminate any orientation or thermal history and maintain an isotropic sheet. The sheet is annealed in an oven at a temperature of (120±2)°C for 1 hour, and then the temperature chamber is closed and slowly cooled to room temperature. During this operation, the sheet is allowed to move freely.

[0290] Next, test pieces were punched out of the pressed sheets. The test specimen geometry was adapted to the modified ISO 37:1994 Type 3 (Fig. 3).

[0291] The sample has a large clamping area to prevent the clamp from slipping, the dimensions are shown in Table 0.

[0292] Table 0: Dimensions of ISO 37:1994 Type 3 as revised

[0293] Dimensions Dimensions (mm) L Starting length between clamps 30.0+ / -0.5 l0 Gauge length 12.5+ / -0.1 l1 Prism length 16.0+ / -1.0 l3 Overall length 70 R1 radius 10.0+ / -0.03 R2 radius 8.06+ / -0.03 b1 Prism width 4.0+ / -0.01 b2 Fixture width 20.0+ / -1.0 h thickness 0.30+0.05 / 0.30-0.03

[0294] The stamping process is carried out in such a way that no deformation, cracking or other irregularities occur in the test piece.

[0295] The sample thickness was measured at three points in the parallel area of ​​the specimen; the minimum measured value of the thickness among these measurements was used for data processing.

[0296] 1. Perform the following steps on a universal tensile testing machine with a controlled temperature chamber and a non-contact extensometer:

[0297] 2. Before starting the test, condition the specimen in a temperature chamber at (80±1)℃ for at least 30 minutes.

[0298] 3. Clamp the test piece on top.

[0299] 4. Close the temperature chamber.

[0300] 5. Close the lower clamp after reaching the temperature of (80±1)℃.

[0301] 6. Allow the sample to equilibrate between the clamps for 1 minute before applying the load and starting the measurement.

[0302] 7. Add a preload of 0.5N at a speed of 5mm / min.

[0303] 8. Stretch the specimen along its major axis at a constant transverse speed (20 mm / min) until the specimen breaks.

[0304] During the test, a 200N load cell was used to measure the load on the specimen. A non-contact extensometer was used to measure the elongation.

[0305] k) Gel content

[0306] The gel count was measured with a gel count device consisting of a measuring extruder ME 25 / 5200V1, 25*25D (with five temperature adjustment zones, the temperature curve was adjusted to 170 / 180 / 190 / 190 / 190°C), an adapter and a slot die (opening 0.5*150 mm). It was attached with a cooling roller unit (13 cm in diameter, temperature set to 50°C), a line camera (CCD 4096 pixels for dynamic digital processing of grayscale images) and a winding unit.

[0307] To measure the gel count content, the material was extruded at a screw speed of 30 rpm, a draw speed of 3-3.5 m / min and a chill roll temperature of 50°C to produce a thin cast film with a thickness of 70 μm and a width of approximately 110 mm.

[0308] On films, the camera has a resolution of 25 μm x 25 μm. The camera works in transmission mode with constant grayscale values ​​(automatically set boundary level = 170). The system is able to judge between 256 grayscale values, from black = 0 to white = 256. For the detection of gels, a dark sensitivity level of 25% is used. For each material, 10 m 2 The average number of gel spots over the film surface area. The line camera was used to distinguish the size of the gel spots according to the following settings:

[0309] Gel size (size of the longest dimension of the gel)

[0310] 300μm to 599μm

[0311] 600μm to 999μm

[0312] 1000μm or more

[0313] 1) GPC measurement

[0314] The molecular weight average (M) was determined by gel permeation chromatography (GPC) according to ISO 16014-1:2003, ISO 16014-2:2003, ISO 16014-4:2003 and ASTM D 6474-12. z 、M W and M n ), molecular weight distribution (MWD) and its width, described by polydispersity index, PDI = M W / M n (where M n is the number average molecular weight, M w is the weight average molecular weight), the formula is as follows:

[0315]

[0316] For a constant elution volume interval ΔV i , where A i and M i and the elution volume V i The associated chromatographic peak slice area and the polyolefin molecular weight (MW), where N equals the number of data points obtained from the chromatogram between the integration limits.

[0317] A high temperature GPC instrument was used, equipped with an infrared (IR) detector (IR4 or IR5 from PolymerChar (Valencia, Spain)) or a differential refractometer (RI) from Agilent Technologies, equipped with 3x Agilent-PLgel Olexis and 1x Agilent-PLgel Olexis Guard columns. 1,2,4-Trichlorobenzene (TCB) (stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol) was used as the mobile phase. The chromatographic system was operated at a column temperature of 160°C and a detector of 160°C with a constant flow rate of 1 mL / min. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus software version 3.3 or PolymerChar GPC-IR control software.

[0318] The column set was calibrated using 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11 500 kg / mol. The PS standards were dissolved at room temperature for several hours. The polystyrene peak molecular weights were converted to polyolefin molecular weights using the Mark Houwink equation and the following Mark Houwink constants:

[0319] K PS =19x 10 -3 mL / g,α PS =0.655

[0320] K PE =39x 10 -3 mL / g,α PE =0.725

[0321] A third-order polynomial fit was used to fit the calibration data.

[0322] All samples had a concentration range of approximately 1 mg / ml and were dissolved at 160°C for 3 (three) hours to dissolve PE in freshly distilled TCB stabilized with 250 ppm Irgafos 168 with continuous gentle shaking.

[0323] Example

[0324] The present invention will be further illustrated by the following non-limiting examples.

[0325] a) Materials

[0326] Table 1 below lists the polymers used to make the multilayer film structures of the examples of the present invention and the comparative examples.

[0327] Table 1:

[0328]

[0329] *MFR5(g / 10min)

[0330] The polymers used are available from the manufacturers listed in Table 1.

[0331] NAV101 is a low density polyethylene (LDPE) post-consumer recycled material blend available from Ecoplast Kunststoffrecycling GmbH. The properties of NAV101 are shown in Table A.

[0332] Table A:

[0333] Ethylene content (weight %) 90.67 isol.C3 content (weight %) 0 C4 content (weight %) 2.23 C6 content (weight %) 2.73 C7 content (weight %) 0.48 iPP content (weight %) 3.89 LDPE content (weight %) 33.00 <![CDATA[Density (kg / m 3 )]]> 923.9 <![CDATA[MFR2(g / 10min)]]> 1.02 <![CDATA[MFR5(g / 10min)]]> 3.57 <![CDATA[MFR 21 (g / 10min)]]> 41.56 SHI2.7 / 210 22.16 eta0.05(Pa·s) 16187 eta300(Pa·s) 618 PI(s-1) 1.46 SH modulus (MPa) 14.3 Gel content (>1000μm) (1 / m2) 16.9 Gel content (600-1000μm) (1 / m2) 175.1 Gel content (300-599) (μm / 1m2) 885.9

[0334] b) Film production

[0335] A three-layer film consisting of a core layer, a skin layer and a seal layer was produced on a Collin 30 lab-scale line. The production was as follows: melt temperature 210°C, total output 7 kg / h, BUR 1:2.5, film thickness 60 μm. The composition and structure of the produced three-layer film are shown in Table 2 below.

[0336] Table 2: Structure of three-layer film

[0337]

[0338] The properties of the three-layer film are shown below in Table 3. The density of each layer was calculated using the formula for the polymer blend provided in "Measurement and Determination Methods" b) above.

[0339] Table 3: Properties of the three-layer film

[0340] CE1 IE1 Density (surface) <![CDATA[kg / m 3 ]]> 918.5 918.5 Density (core layer) <![CDATA[kg / m 3 ]]> 936.4 924.5 Density (sealing layer) <![CDATA[kg / m 3 ]]> 910.2 910.2 Tensile modulus MD MPa 385 207 Tensile modulus TD MPa 455 235 Dart Drop Impact Strength (DDI) g 383 383 SIT ℃ 82 77 Haze % 8.39 7.56

[0341] As can be seen from Table 3, the use of recycled polyethylene in the core layer does not reduce toughness (expressed as dart drop impact strength), but improves the optical properties (haze) and sealability (SIT) of the multilayer polyethylene film.< / gp> < / gp> < / gp>

Claims

1. A multilayer polyethylene film comprising a surface layer, a sealing layer and a core layer located between the surface layer and the sealing layer, in, The core layer comprises a core layer composition, and the core layer composition comprises: a) recycled polyethylene having an MFR2 of 0.1 to 2.0 g / 10 min, measured according to ISO 1133, and a density of 910 to 930 kg / m 3 , b) a multimodal ethylene terpolymer having an MFR2 of from 0.5 to 2.0 g / 10 min, measured according to ISO 1133, and a density of from 910 to 930 kg / m 3 , and a MWD of 2.0 to 7.5 as determined by GPC (gel permeation chromatography), and c) Polyethylene having an MFR5 of 0.1 to 2.5 g / 10 min, measured according to ISO 1133, and a density of 925 to 950 kg / m 3 , and the MWD determined by GPC (gel permeation chromatography) is 8.0 to 35.

0.

2. The multilayer polyethylene film according to claim 1, wherein The surface layer comprises a surface layer composition, and the surface layer composition comprises Multimodal ethylene terpolymer having an MFR2 of from 0.5 to 2.0 g / 10 min, measured according to ISO 1133, and a density of from 910 to 930 kg / m 3 and the MWD measured by GPC (gel permeation chromatography) is 2.0 to 7.5, and / or Low density polyethylene having an MFR2 of 0.1 to 2.0 g / 10 min determined according to ISO 1133 and a density of 910 to 950 kg / m 3 .

3. The multilayer polyethylene film according to any one of the preceding claims, wherein The sealing layer comprises a sealing layer composition, wherein the sealing layer composition comprises Copolymer of ethylene and an alpha-olefin comonomer having 4 to 8 carbon atoms, said copolymer having an MFR2 of 0.5 to 2.0 g / 10 min, measured according to ISO 1133, and a density of 870 to 910 kg / m 3 , and / or Multimodal ethylene terpolymer having an MFR2 of from 0.5 to 2.0 g / 10 min, measured according to ISO 1133, and a density of from 910 to 930 kg / m 3 And the MWD measured by GPC (gel permeation chromatography) is 2.0 to 7.

5.

4. The multilayer polyethylene film according to any one of the preceding claims, wherein The recycled polyethylene is present in the core layer composition in an amount of 50 to 90 wt %, based on the total core layer composition. and / or wherein the multimodal ethylene terpolymer is present in the core layer composition in an amount of 5 to 30 wt %, based on the total core layer composition, and / or Wherein, the polyethylene is present in the core layer composition in an amount of 5 to 30 wt % based on the total core layer composition.

5. The multilayer polyethylene film according to any one of claims 2 to 4, in, The multimodal ethylene terpolymer is present in the skin layer composition in an amount of 80 to 95 wt%, based on the total skin layer composition, and / or Wherein, the low density polyethylene is present in the surface layer composition in an amount of 5 to 20 wt % based on the total surface layer composition.

6. The multilayer polyethylene film according to any one of claims 3 to 5, in, The copolymer of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms is present in the sealant layer composition in an amount of 50 to 90 wt %, based on the total sealant layer composition. and / or Wherein the multimodal ethylene terpolymer is present in the seal layer composition in an amount of 10 to 50 wt%, based on the total seal layer composition.

7. The multilayer polyethylene film according to any one of the preceding claims, wherein The multimodal ethylene terpolymer is a bimodal ethylene terpolymer.

8. The multilayer polyethylene film according to any one of claims 3 to 7, wherein The copolymer of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms is an ethylene-1-octene copolymer.

9. The multilayer polyethylene film according to any one of the preceding claims, wherein The surface layer has a thickness of 1 to 100 μm, and / or Wherein, the thickness of the core layer is 10 to 200 μm, and / or Wherein, the sealing layer has a thickness of 1 to 50 μm.

10. The multilayer polyethylene film according to any one of the preceding claims, wherein The multilayer polyethylene film has a tensile modulus in the machine direction (MD) measured on a 60 μm test film according to ISO 527-3 of 150 MPa or more, and / or a tensile modulus in the transverse direction (TD) measured on a 60 μm test film according to ISO 527-3 of 150 MPa or more.

11. The multilayer polyethylene film according to any one of the preceding claims, wherein The multilayer polyethylene film has a dart drop impact strength (DDI) of greater than 300 g and / or a SIT (seal initiation temperature) of less than 82° C., the dart drop impact strength being determined according to ISO 7765 on a 60 μm test film.

12. A method for producing a multilayer polyethylene film according to any one of the preceding claims, wherein: The skin layer, the seal layer and the core layer are co-extruded.

13. A core layer composition comprising: a) Recycled polyethylene having an MFR2 of 0.1 to 2.0 g / 10 min, measured according to ISO 1133, and a density of 910 to 930 kg / m 3 , b) a multimodal ethylene terpolymer having an MFR2 of from 0.5 to 2.0 g / 10 min, measured according to ISO 1133, and a density of from 910 to 930 kg / m 3 , and a MWD of 2.0 to 7.5 as determined by GPC (gel permeation chromatography), c) Polyethylene having an MFR5 of 0.1 to 2.5 g / 10 min, measured according to ISO 1133, and a density of 925 to 950 kg / m 3 , and the MWD determined by GPC (gel permeation chromatography) is 8.0 to 35.

0.

14. Use of the core layer composition according to claim 13 as a core layer of a multilayer polyethylene film to improve the haze and SIT of the multilayer polyethylene film.

15. An article comprising the multilayer polyethylene film according to any one of claims 1 to 11 or the core layer composition according to claim 13.

Citation Information

Patent Citations

  • Polyethylene based laminated film structure with barrier properties

    CN109070558A

  • Multilayer polymer film

    CN111315567A

  • Collation shrink film

    CN113661062A

  • Multilayer film containing two outer top layers in LDPE, a highly crystalline propylene core layer, and polypropylene adhesion promoting layers useful in label production

    DE10228273A1

  • Polyolefin resin blends for high stress cracking resistance and good processability

    EP3626774A1